Correlation Between Organizational Structure, Leader Behavior and Personality with Citizen Beahavior about The Environment in an Islamic Perspective - Madina, Sahmin (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This research aims to find out the correlation between organizational structure, leader behavior and personality and behavior of citizen about the environment in Islamic perspective. The research used quantitative method with survey design by taking 150 lecturers of IAIN Sultan Amai Gorontalo as the sample. Four variables were measured, namely behavior of citizen about the environment in Islamic perspective (rel.97), organizational structure (rel.95), leader behavior (rel.92), and personality (rel.94). It used two-way ANOVA to analyze the data. The results showed that there was positive and significant correlation among those variables, even though it has been controlled by second-order correlation. Therefore, it could be concluded that organization structure, leader behavior and personality became consideration to improve behavior of citizen about the environment in Islamic perspective.